1994
DOI: 10.1007/bf01247462
|View full text |Cite
|
Sign up to set email alerts
|

An application of MIB antibody to the retrospective study of melanomas of oral mucosa and facial skin

Abstract: A new monoclonal antibody prepared against a fragment of Ki-67 antigen MIB, from Dianova, was applied for investigation of malignant melanomas of facial skin (25 cases) and the oral cavity (25 cases), which were routinely embedded in paraffin. The values of the Ki-67 index (expressed as a percentage of positive nuclei) were correlated with TNM characteristics of tumors and patient survival. Significant correlation was found between the Ki-67 index and the level of lymph node involvement (N value), the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Which problems have to be considered with regard to the determination of these immunohistochemical markers and to our statistical evaluation? A prognostic relationship of the seven significant markers of this study, except H2‐8‐10, has been reported 3,8,11,12,16,19–25,27,30–36 or at least suspected 7,37 , 38 in the literature. Our data, obtained by tests of a larger number of tumours, confirms these earlier results.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Which problems have to be considered with regard to the determination of these immunohistochemical markers and to our statistical evaluation? A prognostic relationship of the seven significant markers of this study, except H2‐8‐10, has been reported 3,8,11,12,16,19–25,27,30–36 or at least suspected 7,37 , 38 in the literature. Our data, obtained by tests of a larger number of tumours, confirms these earlier results.…”
Section: Discussionsupporting
confidence: 53%
“…The expression of HLA‐DQ and HLA‐DP antigens on primary and metastatic melanomas has been described 18 . The staining characteristics of the proliferation marker Ki‐67 have been studied in primary and metastatic melanomas 3 , 19–28 . The reactivity pattern of antimacrophage antibody EBM‐11 with various tissues, including skin has been described 13…”
Section: Methodsmentioning
confidence: 99%
“…A correlation between mitotic indices and the Ki-67 positivity in malignant melanomas has been observed by several investigators (40,43,45). Some investigators have also studied the correlation of Ki-67 immunostaining results and tumor size and/ or prognosis in malignant melanoma of the skin (22,23,(40)(41)(42)(43)(44). Tbese studies are summarized in Table 6.…”
Section: Studymentioning
confidence: 88%
“…In primary malignant melanoma of the skin the proliferative activity has also been studied by several methods. In some of these studies mitotic counts, flow cytometry and immunohistochemical staining with Ki-67 antibody have had prognostic value (18)(19)(20)(21)(22)(23). However, to our knowledge, the prognostic value of Ki-67 immunostaining has not been studied utilizing multistep regression analysis models and the follow-up times of the patients have been rather short.…”
mentioning
confidence: 99%
“…Previous studies of melanoma have investigated the ability of Ki‐67 to provide useful prognostic information 11–16. Because Ki‐67 is not expressed in resting, G0 cells, but is expressed from the mid‐G1 phase of the cell cycle through S, G2, and M phases, it is considered to be a reliable marker of cell proliferation.…”
mentioning
confidence: 99%